Canon 983 § 1: Certificates of first Reconciliation - Souckar, Michael A. (Roman Replies and CLSA Advisory Opinions 2013, 2013)
On the day following the First Confession of the school and religious education studentes, Father Smith, the recently appointed pastor of Saint Anthony Parish, finds on his desk a stack of "Certificates of First Reconciliation." Accompanying the certificates is a memo from the Director of Religious Education asking Father Smith to sign the certificates, as the former pastor always did. Is Father Smith free to do this?